Perioperative concerns in a patient with suspected Creutzfeldt - Jakob disease: A case report and review of literature - Kathiravan Thangavel; Chhavi Sawhney; Anjishnujit Bandyopadhyay (Saudi Journal of Anaesthesia, 2024)
A case of Creutzfeldt-Jakob Disease (CJD), a rare prion disease, posted for surgery is a clinically challenging scenario for an anesthesiologist. In addition to weighing in the consequences of using general versus neuraxial anesthesia for a patient of such a progressive neurodegenerative disorder, the anesthesiologist must also meticulously plan and institute a robust infection control protocol, keeping in mind that prion diseases are transmissible and highly resistant to the standard sterilization process. We hereby report the successful anesthetic management of a 57-year-old patient with suspected CJD presented with intertrochanteric fracture femur for closed reduction and internal fixation and also review the existing literature regarding the anesthetic management of a definite or suspected case of CJD.